Simultaneous Surgery and Management in Patients with Chronic Cholecystitis and Gynecological Diseases - Mamakeev Kanat, Ashimov Zhanybek, Talaibekova Aiperi, Ashimov Isabek, Kadyrov Adilet,Altynai Zhumabekova (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Simultaneous surgery for chronic cholecystitis and gynecological diseases is a complex clinical scenario that requires careful consideration of the operation and anesthetic risks involved. This study aimed to evaluate the outcomes of patients who underwent simultaneous operations for these combined conditions at the National Clinical Center of the Ministry of Health of the Kyrgyz Republic between 2019 and 2023. Materials and Methods: A total of 132 patients were divided into two groups based on the surgical approach and volume of the operation: Group I (n = 63, 47.7%) underwent laparoscopic cholecystectomy and gynecological laparoscopy (LC + GL), while Group II (n = 69, 52.3%) underwent LC and open cholecystectomy (LC + OC). Results: The mean age was 53.5 ± 2.8 years for Group 1 and 52.2 ± 2.7 years for Group 2, with no significant age difference between the groups (P > 0.05). The most common gynecological diseases among the patients were uterine fibroids (52.2%), adenomyosis (30.3%), and ovarian cysts (11.4%). In 35 (55.5%) patients who underwent LC, surgeons employed conventional methods for pelvic organ operations, utilizing a 10 mm periumbilical trocar for the laparoscope and two 5 mm trocars in the iliac regions. Conclusion: The results suggest that simultaneous surgery for chronic cholecystitis and gynecological diseases can be performed safely, reducing the patient’s physical burden and treatment and recovery time. However, further research is needed to better understand the risks and benefits of this approach in different patient populations.